2013
DOI: 10.5194/nhess-13-597-2013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of seismo-electric anomalies using magnetic data in Taiwan

Abstract: The Parkinson vectors derived from 3-component geomagnetic data via the magnetic transfer function are discussed with respect to epicentre locations and hypocentre depths of 16 earthquakes (M ≥ 5.5) in Taiwan during a period of 2002–2005. To find out whether electric conductivity changes would happen particularly in the seismoactive depth ranges, i.e. in the vicinity of the earthquake foci, the frequency dependent penetration depth of the electromagnetic waves (skin effect) is taken into account. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 40 publications
(43 reference statements)
1
16
0
Order By: Relevance
“…Seismo-magnetic anomalies have been widely observed and reported in many major earthquakes (Fraser-Smith et al 1990;Bernardi et al 1991;Molchanov et al 1992;Kopytenko et al 1993;Hayakawa et al , 1999Hayakawa et al , 2000Kawate et al 1998;Gotoh et al 2002;Hattori et al 2002Hattori et al , 2004aHattori et al , b, 2013Liu et al 2006;Molchanov and Hayakawa 2008;Chen et al 2009Chen et al , 2010Chen et al , 2011aChen et al , 2012Chen et al , 2013aHan et al 2011;Wen et al 2012). These anomalies are generally considered to be caused by the momentary existence of electric currents along faults (Yen et al 2004), sudden changes in conductivity (Zeng et al 1995;Merzer and Klemperer 1997) and/or fluctuations in susceptibility near epicenters (Stacey 1962;Nagata 1970;Liu et al 2006;Wen et al 2012) due to the accumulation of earthquake-related stress on nearby rock beds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seismo-magnetic anomalies have been widely observed and reported in many major earthquakes (Fraser-Smith et al 1990;Bernardi et al 1991;Molchanov et al 1992;Kopytenko et al 1993;Hayakawa et al , 1999Hayakawa et al , 2000Kawate et al 1998;Gotoh et al 2002;Hattori et al 2002Hattori et al , 2004aHattori et al , b, 2013Liu et al 2006;Molchanov and Hayakawa 2008;Chen et al 2009Chen et al , 2010Chen et al , 2011aChen et al , 2012Chen et al , 2013aHan et al 2011;Wen et al 2012). These anomalies are generally considered to be caused by the momentary existence of electric currents along faults (Yen et al 2004), sudden changes in conductivity (Zeng et al 1995;Merzer and Klemperer 1997) and/or fluctuations in susceptibility near epicenters (Stacey 1962;Nagata 1970;Liu et al 2006;Wen et al 2012) due to the accumulation of earthquake-related stress on nearby rock beds.…”
Section: Introductionmentioning
confidence: 99%
“…These anomalies are generally considered to be caused by the momentary existence of electric currents along faults (Yen et al 2004), sudden changes in conductivity (Zeng et al 1995;Merzer and Klemperer 1997) and/or fluctuations in susceptibility near epicenters (Stacey 1962;Nagata 1970;Liu et al 2006;Wen et al 2012) due to the accumulation of earthquake-related stress on nearby rock beds. Chen et al (2013a) computed Parkinson vectors using the 3-component data recorded at the CCU station via the magnetic transfer function (Parkinson and Jones 1979) to examine the change in conductivity relating to earthquakes. It was found that the Parkinson vectors generally direct toward source locations, where underlying conductivity is higher than its neighborhood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the Taiwan recorded geomagnetic data is recorded in high-quality. These valuable data have been utilized to correct the solar effects when the geomagnetic survey was processed in the Taiwan area Chen et al 2014;Hsieh et al 2014) and to study interesting phenomena associated particularly with seismo-magneitc anomalies (Chen et al , 2011(Chen et al , 2013Wen et al 2012). Chen et al (2004) found that changes in the annual geomagnetic field values in Taiwan approached 0 nT about 2 years before the Chi-Chi earthquakes (on 20 September 1999; UTC).…”
Section: Introductionmentioning
confidence: 99%
“…1-Hz geomagnetic total intensity data recorded at 2 monitoring stations (TT and HC) in Taiwan Chen et al 2009Chen et al , 2013 and 1 remote station (KNY) in Japan ( Fig. 1) were utilized in this study to investigate geomagnetic disturbances triggered by 3 typhoons over the western Pacific Ocean in September 2008.…”
Section: Introductionmentioning
confidence: 99%